PENGEMBANGAN PAKET NEKAMEDIA MATEMATIKA KURIKULUM 2013 MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII SMP DI KOTA SURAKARTA - Anggraini, Putri Nurika; Budiyono, Budiyono; Slamet, Isnandar (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: This study was aimed to obtain 2013 Curriculum of mathematics mutlimedia kit using Problem Based Learning (PBL) model in plane geometry lesson of eighth grade junior high school in Surakarta which is considered as a valid, practical, and effective to be applied for learning. Furthermore, the goal was to discover whether the studentâs achievement of plane geometry lesson using the developed mutlimedia kit is better than using the prior product. The study type was Research and Development (R & D) to generate and verify product effectiveness. Study procedure refers to modified Four-D model (Define, Design, Develope, Disseminate) which is appropriate to study requirements and limitations. In the effort to obtain a valid, practical, and effective mutlimedia kit to be applied for learning, we used questionnaire to obtain these following data: (1) comments and recommendations from experts about mutlimedia kit; (2) learning feasibility score by teachers and follow-up recommendations; (3) activity score of students and follow-up recommendations; and (4) appreciation and eagerness level of students toward mutlimedia kit. We used test as an attempt to figure out whether the studentâs achievement of plane geometry lessons using the developed mutlimedia kit is better than using the prior product. Study results conclude that mutlimedia kit is valid, practical, and effective to be used in learning activity. Percentage of learning feasibility by teachers is 92%, percentage of studentsâ activities is 80%, and percentage of students who appreciate and want to use mutlimedia kit is 80%. After being tested, final studentâs achievement of experimental class is better than final studentâs achievement of control class.Key words: mathematics mutlimedia kit, 2013 Curriculum, Problem Based Learning (PBL) model, plane geometry.